Analyzing the environmental readiness of coffee shop entrepreneurs: A study using the PLS-SEM approach and the theory of reasoned action - Istighfarani, Syifa (EcoProfit: Sustainable and Environment Business, 2025)
Background: The rapid growth of the coffee industry has increased consumption and the generation of spent coffee grounds waste, which poses environmental risks while offering economic potential. Although previous studies have discussed the hazards and benefits of this waste, comprehensive research on coffee shop entrepreneurs’ readiness to adopt environmentally friendly behavior remains limited. This study aims to examine their readiness by analyzing the influence of awareness, knowledge, attitude, intention, and actual behavior, based on the Theory of Reasoned Action. Methods: A quantitative approach with a cross-sectional design was used. Data were collected in 2022 from 200 coffee shop entrepreneurs in Jakarta and Bekasi, selected as central coffee business areas. Partial Least Squares (PLS) analysis was conducted, including outer model, goodness-of-fit, and inner model tests. Findings: The results showed that environmental awareness had no significant direct or indirect effect on environmentally friendly behavior. In contrast, knowledge significantly influenced the formation of positive attitudes, which mediated the relationship with intention and actual behavior. These results underscore the need to distinguish between awareness and knowledge, as only the latter demonstrated a meaningful impact on behavior formation. Well-informed attitudes enhanced behavioral intention, which in turn significantly influenced actual pro-environmental behavior. These findings validate the Theory of Reasoned Action and extend its applicability in explaining pro-environmental behavior adoption in waste-management-based entrepreneurship, particularly in coffee shop businesses. Conclusion: The study highlights the importance of environmental and entrepreneurial education regarding both the risks and economic potential of spent coffee grounds. Government support is needed to promote education, build enabling systems, and provide infrastructure to foster environmentally responsible behavior. Novelty/Originality of this article: This study offers a novel contribution by examining coffee shop entrepreneurs' environmental readiness using the Theory of Reasoned Action and a PLS-SEM approach. Unlike prior studies that focused on the risks and benefits of spent coffee grounds, this research explores the behavioral pathway from awareness and knowledge to actual pro-environmental practices, highlighting the distinct roles of both.